PREDICTION STAGES OF THE DIFFICULT INERTIA SYSTEM BEHAVIOR WITH THE USE OF THE DEVELOPED SYSTEM MODEL - Vasyl V. Bychenkov (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni)
The difficult inertia systems prediction question with the use of the difficult systems models is considered in the article. It is indicated, that the entrance model data consistоf three groups: the arguments group when argument's values are determined by a researcher, the arguments group when argument's values are observed by a researcher, but researcher doesn't have an impact on this arguments, the arguments group when values are not taken into account during prediction. The system output data is – the difficult system reaction on еруarguments effect. From knowledge of the external factors effect on the system history and system response toеру effect - there is possibility of creating the difficult inertia system model. The model creation and use algorithm for prediction of the difficult inertia system behavior is offered in the article. It is marked, that the algorithm consists of the three stages: developing difficult system model variants; checking difficult system model variants efficiency; using difficult inertia system model during prediction. The use of the model creation and use algorithm for prediction of the difficult inertia system behavior will allow developing models, which will meet requirements of adequate calculations accuracy which are conducted and adequacy execution of the represented processes in the model to the processes which exist in the difficult inertia system.